A minimally invasive endoscopic transnasal retropterygoid approach to the upper parapharyngeal space: anatomic studies and surgical implications. Issue 11 (1st October 2019) - Liu, Juan; Sun, Xicai; Liu, Quan; Gu, Yurong; Li, Houyong; Zheng, Chunquan; Wang, Dehui; Fernandez‐Miranda, Juan C.; Snyderman, Carl H.; Yu, Hongmeng
Abstract : Background: Surgery remains the mainstay of treatment for lesions in the parapharyngeal space. However, gaining access to the parapharyngeal space is often challenging. In this study we aim to describe a minimally invasive technique of approaching the upper parapharyngeal space through an endoscopic transnasal retropterygoid approach, based on anatomic studies and surgeries. Methods: Six fresh human cadaver heads were prepared for anatomic study at the Surgical Neuroanatomy Laboratory of the Center for Cranial Base Surgery within the Department of Neurological Surgery at the University of Pittsburgh School of Medicine. Three clinical cases seen in the Department of Otolaryngology, Eye, Ear, Nose, and Throat Hospital, Shanghai Medical College of Fudan University, were used to illustrate the technique and feasibility of this approach and to assess its indications, advantages, and drawbacks. Results: The medial pterygoid plate is the primary landmark of the endoscopic transnasal retropterygoid approach to the upper parapharyngeal space. Access to the upper parapharyngeal space could be obtained by removing the mucosa on the medial pterygoid plate and the mucosa below the pharyngeal orifice of the Eustachian tube. The 3 patients in our study tolerated the procedure well and had no serious complications after surgery. Conclusion: The anatomic data and clinical cases in this study confirm that an endoscopic transnasal retropterygoid approach is a feasible and effective surgical treatment for selected tumors in the upper parapharyngeal space.